1994
DOI: 10.1037/0735-7044.108.5.972
|View full text |Cite
|
Sign up to set email alerts
|

Tegmental pedunculopontine lesions in rats decrease saccharin's rewarding effects but not its memory-improving effect.

Abstract: The tegmental pedunculopontine nucleus (TPP) of the brainstem has been identified as a critical substrate for both opiate and food reward in nondeprived rats. In this study of rats, TPP lesions blocked saccharin-conditioned place preferences, in both the presence and the absence of water deprivation. TPP lesions also attenuated the unconditioned intake of saccharin and water over several hours after recovery from food and water deprivation. TPP lesions did not block saccharin preferences over water in short-du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…According to these authors, this different pathway would explain the fact that the same lesions in the PPN that impair place preference learning produced by morphine do not block TAL when it is induced by morphine or LiCl (Bechara et al, 1993;Stefurak & Van der Kooy, 1994). The discrepancy between these studies and the results presented in experiment 1 of this article can be explained in terms of the TAL procedures used in the two cases.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…According to these authors, this different pathway would explain the fact that the same lesions in the PPN that impair place preference learning produced by morphine do not block TAL when it is induced by morphine or LiCl (Bechara et al, 1993;Stefurak & Van der Kooy, 1994). The discrepancy between these studies and the results presented in experiment 1 of this article can be explained in terms of the TAL procedures used in the two cases.…”
Section: Discussioncontrasting
confidence: 55%
“…In summary, the data for the lesioned animals in the short-term TAL task cannot be the result of sensory or motor deficits. It is likely that the PPN is involved in reinforcement processes (Olmstead, Munn, Franklin, & Wise, 1998;Stefurak & Van der Kooy, 1994), but this study shows that it may also be important for certain types of learning. In particular, it could be thought that PPN lesions play a specific role in aversive learning since they impair acquisition of short-term TAL characterized by the simultaneous presentation of the gustatory and visceral stimuli that requires rapid transmission of both sensory modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Food or water intake, not only increases accumbal dopamine release, but also simultaneously enhances the extracellular levels of acetylcholine in the VTA [6], [8], [9]. In addition, lesion of the cholinergic projections from the LDTg to the VTA decreases nicotine and cocaine self-administration [6], [39], inhibits the motivational effects of opiates [40] and attenuates the intake of saccharin and water in rats [41], blocks the rewarding properties of food [40] and impairs sexual activity in naïve male rats [42]. Furthermore, it has been shown that alcohol intake in high alcohol-preferring rats causes a concomitant increase in ventral tegmental acetylcholine and accumbal dopamine [7].…”
Section: Discussionmentioning
confidence: 99%
“…Reinforcers are stimuli that are approached, selfadministered, attained, or preserved in some way; they are activities that are relatively preferred or deprived compared to baseline level. This fundamental motivational characteristic of reinforcing stimuli is sometimes referred to as the primary or "unconditioned" reinforcing property of those stimuli (Nader et al 1997;Stefurak and van der Kooy 1994).…”
mentioning
confidence: 99%